Smallholder families and commercial farmers’ perception on Agroforestry Systems in Tomé-Açu, Pará, Brazil (Sustainability in Debate, 2017)
This article evaluates the agroforestry perception of smallholders and agrobusiness farmers in the town of Tomé-Açu, State of Pará. The perception of farmers was important to build relationships with nature during the implementation and management of agroforestry systems (AFS), however, more work needs to be done in order to better understand this perception. For this purpose, quantitative and qualitative approaches were applied, interviews with semi-structured scripts were carried out, crosscut walks in rural areas with direct observation and annotations were done in a field diary. Data were analyzed by descriptive statistics in the SPSS 19.0 program. The farmers’ perceptions about AFS are distinct. The environmental feature is considered by smallholders due to their historical-cultural view of systems management and the necessity for shadowing and valorization of ecosystem services. The commercial concerns are more relevant to agrobusiness farmers It is worth noting that, in view of the analysis, the support of CAMTA (Mixed Agricultural Cooperative of Tomé-Açu), APPRAFAMTA (Association of Rural Producers and Producers of Family Agriculture of Tomé-Açu) and educational and research institutions is important in the dissemination of information and the exchange of experiences for the agroecological transition.